Psychological Determinants of Emotional Eating in Adolescence - NGUYEN-RODRIGUEZ, SELENA T. (2009)
Emotional eating is conceptualized as eating in response to negative affect. Data from a larger study of physical activity was employed to examine the associations among specific emotions/moods and emotional eating in an adolescent sample. Six-hundred and sixty-six students of diverse backgrounds from 7 middle schools in Los Angeles County participated. Cross-sectional analysis revealed no gender differences in emotional eating, and showed that perceived stress and worries were associated with emotional eating in the total sample. Gender stratified analyses revealed significant associations of perceived stress, worries and tension/anxiety to emotional eating for girls, while only confused mood was related to emotional eating in boys. These findings bear potential implications for the treatment and prevention of pediatric obesity and eating disorders because they suggest that interventions would benefit from incorporation of stress-reduction techniques and promotion of positive mood.